Self-assessed clinical competence: a comparison between students in an advanced dental education elective and in the general clinic - Lindemann, Robert A.; Jedrychowski, Joseph (European journal of dental education, 2002)
A six‐month final‐year elective, based on an advanced education in general dentistry (AEGD) model, was conducted in an AEGD Clinic to enable dental students to treat patients in a generalist comprehensive setting. The purpose of this study was to evaluate the elective with regard to students' self‐assessed clinical skills, as self‐assessment is recognized as a means to maintaining competency. Pre‐ and post‐experience surveys were administered to ‘AEGD elective students’ (n=13) and a comparison group of ‘control dental students’ (n=18) under a discipline‐based clinical curriculum. The survey instrument consisted of 75 self‐rated statements on a wide range of clinical and patient management skills. Pre‐experience means were not statistically different. The AEGD elective students' post‐experience group mean was significantly higher than the control dental students' mean (P=0.02, ANOVA) which reflects significant (P<0.05) increases in 9 of 13 AEGD elective students' individual survey means compared to 4 of 18 control dental students' means. Both groups had pre‐experience means of 2.9 or below on the same 9 statements, indicating poor self‐rated skills. Four of 9 AEGD elective students' post‐experience means significantly (P<0.05) increased, while only 1 of 9 control dental students' means increased. The data suggests that AEGD elective students were more confident in their clinical abilities and patient management skills than control dental students and they also reported greater improvement in low‐rated skills. When adequate parameters were maintained that enhanced the accuracy of self‐assessment, students appeared to rate their skill levels seriously. Independent self‐assessment may be an important component of life‐long learning.